Characterization of date palm frond as a fuel for thermal conversion processes - Sadig, H. (EDP Sciences, 2017)
Date palm fronds (DPF) have similar physical appearances to those of oil palm fronds and coconut palm fronds, which have been reported as having good potential as a source of energy through thermochemical conversion of biomass. However, nearly no report has been found pertaining to thermochemical properties of DPF. Hence, it has remained unclear whether DPF can become suitable feedstock for power generation. This study investigated the characteristics of DPF as a potential solid fuel for heat and power generation through various thermal conversion processes. DPF samples from selected sites in Sudan and Saudi Arabia were tested. The ultimate and proximate analyses and the calorific value of DPF were measured, and the results were compared with low to medium-rank coals and other common biomass materials. The calorific value range for DPF samples was found to be between 16.2 to 16.9 MJ/kg. The ultimate analysis of DPF samples revealed that more than 75 of their mass was composed of volatile materials, while the ash content in all samples was found to be less than 15. The range of elementary carbon, hydrogen, nitrogen, sulfur and oxygen in DPF samples was found to be typical to that in biomass. The thermal decomposition trends the samples indicated the high reactivity of DPF with rising temperatures due to high holocellulose content. No distinctive differences in test results were observed between samples from Saudi Arabia and Northern Sudan. Overall, it was found that all DPF samples used in this study fulfilled the typical requirements for development and utilization as a solid fuel. © The authors, published by EDP Sciences, 2017.